Boosting Therapeutic Effect of Turmeric, Coffee, and Chili Extracts Through Experimental Design and Encapsulation as Nanostructured Lipid Carriers for Novel Heath Supplements - Pratchaya Tipduangta; Phennapha Saokham; Jutamas Jiaranaikulwanitch; Siriporn Okonogi; Chadarat Ampasavate; Kanokwan Kiattisin (Plants)
This study investigates the potential synergistic effects of extracts from Curcuma longa (turmeric), Coffea arabica (Arabica coffee beans), and Capsicum annuum (chili peppers) in reducing oxidative stress and inflammation, which are associated with metabolic disorders such as obesity, diabetes, and cardiovascular diseases. Using a systematic design of experiment (DoE) optimization approach, an optimal extract ratio of 1:3:4 (turmeric: coffee: chili) was identified. The efficacy of the extract combination was assessed through various antioxidant assays, inhibition of inflammation-related gene expression, and safety testing via the 3-(4,5-dimethylthazolk-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay. The extract combination showed higher antioxidant activity and comparable anti-inflammatory effects relative to each single extract. Additionally, the extract combination demonstrated effective activity compared with turmeric extract while using a lower concentration, resulting in reduced cytotoxicity. The optimized extract combination was successfully incorporated into nanostructured lipid carriers (NLCs) with a hydrodynamic diameter of 258.0 ± 10.2 nm, which effectively redisperses after the spray-drying process with increased diameter to 349.8 ± 49.6 nm. Under stress conditions, the stability of curcumin and capsaicin in dried-NLCs was maintained. In summary, the optimized extract-loaded NLCs formulation, achieved through a multistage approach, shows promise in mitigating oxidative stress and inflammation, suggesting its potential as a valuable daily dietary supplement.